Optimization and multisequencing of electronic system analysis by methods of odd classification - Шибицкий, В. П.; Савчук, Н. Н. (Proceedings of National Aviation University (archive), 1998)
Modern computers allow to simulate electronic systems in accordance with classical methods of analysis and synthesis based on the theory of odd classification of information objects without forming intermediate matrix, typological and other models